2020
DOI: 10.3390/ijerph17176384
|View full text |Cite
|
Sign up to set email alerts
|

Get Vigorous with Physical Exercise and Improve Your Well-Being at Work!

Abstract: The aim of this study is to investigate whether people who exercise regularly have higher levels of psychological well-being at work. Doing physical exercise is a habit that not only has consequences for physical and mental health, but it can also have positive consequences for organizations because physical exercise makes it easier for the employee to recover from physical, mental, and emotional effort during the workday, thus showing higher levels of engagement the next day. Through the analysis of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
12
2
Order By: Relevance
“…In fact, efficiently and with good management, you can become self-sufficient [10]. This situation is due to the fact that a workplace is an environment conducive to the promotion of physical activity aimed at greater productivity and improved health, all due to its great physical and psychological benefits [11][12][13].…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, efficiently and with good management, you can become self-sufficient [10]. This situation is due to the fact that a workplace is an environment conducive to the promotion of physical activity aimed at greater productivity and improved health, all due to its great physical and psychological benefits [11][12][13].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Third, workplace well-being programmes have a positive impact on psychosocial aspects, such as emotional stability, optimism, enthusiasm and psychological well-being [31], trust [32], a greater perception of the ability to control memory [33], the will to work, the feeling of well-being and interpersonal relationships [24], and an improvement in the resilience of employees [34]. Furthermore, Gil-Beltrán et al [11] showed that regular physical activity is required to reduce stress levels, improve job satisfaction levels and make job emotions more positive. Likewise, employees who exercise are more empathetic and engaged compared to sedentary employees [35].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…People who exercise regularly have a higher level of mental health. Physical exercise can reduce work pressure and improve job satisfaction and happiness ( 235 ). Aerobic exercise has been shown to significantly improve serum ALT, aspartate aminotransferase (AST), and NAFLD activity scores in NAFLD patients and has a certain effect on TG ( 236 , 237 ).…”
Section: Discussionmentioning
confidence: 99%
“…During confinement, it was possible to observe an increase in the offer of digital channels that help the guided practice of physical activity throughout the use of safe, simple and easy to implement programs and applications that cover activities related to cross-fit, yoga or dance activities for the general population or for the improvement of physical and mental well-being in older adults [42]. According to the findings in this successful case study, it can be concluded that it is highly recommended implementing these hybrid corporate well-being programmes, due to all the physical, mental and social benefits it brings to employees and, therefore to the company [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], even more in this COVID-19 times. This is in line with Núñez-Sánchez et al (2021) [49], who concluded that physical inactivity and increased sedentary lifestyles triggered by Covid-19 and teleworking are having negative consequences for the physical and mental health of employees, which is why it is essential for companies that want to look after the health of their employees, while they work at home, to adapt their wellness programmes to the new situation as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Corporate well-being programmes also have a positive impact on psychosocial aspects, such as emotional stability, optimism, enthusiasm, and psychological well-being [31], trust [32], greater perception of the ability to control memory [33], the willpower to work, the feeling of well-being and interpersonal relationships [28], and with an improvement in the resilience of employees [34]. In addition, Gil-Beltrán, Meneghel, Llorens and Salanova [35] showed that, in order to reduce stress levels, improve job satisfaction levels, and make work emotions more positive, physical activity must be performed regularly.…”
Section: Corporate Wellnessmentioning
confidence: 99%